PERAN BRAND IMAGE DALAM MEMEDIASI KUALITAS PRODUK , IKLAN TERHADAP MINAT BELI ULANG - Indrawan, Yoga; Winadi Prasetyoning Tyas, Ari Anggarani (Jurnal Ekonomi : Journal of Economic, 2025)
Product Quality, Advertising, and Repurchase Interest in Aqua Bottled Drinking Water (AMDK) Products In this study, we will investigate and test brand image as an exogenous variable, which acts as a mediating variable, and repurchase intention as an endogenous variable. This research is aimed at customers in the Rawa Buaya area who purchase and consume bottled mineral water (AMDK). This research was driven by increasingly advanced developments and the community's need for drinking water which is very important. As a result, aspects of product quality and advertising that affect brand image are determining factors in consumer decisions to repurchase or not. Factors that need to be considered related to bottled mineral water (AMDK) in the Rawa Buaya area include product quality, advertising, brand image. This research involved 120 respondents who were selected through the Non Probabality Sampling strategy to examine the relationship between factors of repurchase intention. To examine the direct and backward relationship between the different factors, a structural equation modeling (SEM) technique with partial least squares (PLS) was used. The consequences of this study indicate that (1) there is no direct effect between Product Quality and Repurchase Intention, (2) there is a very large direct impact between Advertising Purpose and Repurchase, (3) there is a direct influence effect between brand image and Purchase Expectations Again, (4) there is an influence between product quality and brand image, (5) there is a significant direct relationship between advertising and brand image, (6) there is an influence between product quality through brand image on repurchase intention, (7) there is influence between advertising through brand image on Repurchase Intention.